Tabelas de vida de Orius insidiosus (Say, 1832) (Hemiptera: Anthocoridae) predando Aphis gossypii Glover, 1877 (Hemiptera: Aphididae) em diferentes cultivares de algodoeiro - de Bortoli, S.A.; Oliveira, J.E.M.; dos Santos, R.F.; Silveira, L.C.P. (My University, 2008)
The life table parameters were studied for Orius insidiosus on the three cotton plant cultivars Antares, CNPA7H and Acala 90 (respectively, without tricome, medium tricome density and high tricome density). This study showed that the type of cultivar can strongly influence the life-table parameters. The intrinsic rate (rm) was 0.088 (on Antares), 0.081 (CNPA7H) and 0.079 (on Acala 90), which was expected as these differences were also observed for development time, survival, fecundity and longevity on the cultivars. The reproductive rate (Ro) was 18.53 on the Antares cultivar, but showed less difference for CNPA7H (12.26) and Acala 90 (12.95). The development time was 33.9, 30.62 and 32.13 days for Antares, CNPA7H and Acala 90, respectively. The age-specific survival was similar until the 12th day. Maximum survival was 60 days on the Antares cultivar. Females usually began to oviposit after 16 days on the Antares cultivar and the after 19 days day on CNPA7H and Acala 90.
Life tables and fertility of Orius insidiosus (Say) preying on Aphis gossypii Glover on differents cotton plant cultivars